Experimental cancer rat models - Yu. D. Vinnichuk; O. M. Platonov; O. O. Gryshchuk; S. V. Komisarenko (The Ukrainian Biochemical Journal, 2025)
Experimental rat models are widely used in cancer research. This is facilitated by the diversity of existing inbred animal lines and their relatively low cost. The purpose of this review was to analyze and systematize the publications 2000-2024 selected in PubMed and in national author databases on various cancer rat models. The advantages, disadvantages, and prospects of using these models in the study of different aspects of cancer pathology are discussed. The information will help researchers choos an adequate experimental rat model to study the mechanisms of cancer development and the possibility of its treatment.